The Ferritin-Like Dps Protein Is Required for Salmonella enterica Serovar Typhimurium Oxidative Stress Resistance and Virulence - Halsey, Thomas A. (American Society for Microbiology, 2004)
Resistance to phagocyte-derived reactive oxygen species is essential for Salmonella enterica serovar Typhimurium pathogenesis. Salmonella can enhance its resistance to oxidants through the induction of specific genetic pathways controlled by SoxRS, OxyR, σ(S), σ(E), SlyA, and RecA. These regulons can be found in a wide variety of pathogenic and environmental bacteria, suggesting that evolutionarily conserved mechanisms defend against oxidative stress both endogenously generated by aerobic respiration and exogenously produced by host phagocytic cells. Dps, a ferritin-like protein found in many eubacterial and archaebacterial species, appears to protect cells from oxidative stress by sequestering iron and limiting Fenton-catalyzed oxyradical formation. In Escherichia coli and some other bacterial species, Dps has been shown to accumulate during stationary phase in a σ(S)-dependent fashion, bind nonspecifically to DNA, and form a crystalline structure that compacts and protects chromatin from oxidative damage. In the present study, we provide evidence that Dps protects Salmonella from iron-dependent killing by hydrogen peroxide, promotes Salmonella survival in murine macrophages, and enhances Salmonella virulence. Reduced numbers of dps mutant bacteria in the livers and spleens of infected mice are consistent with a role of Dps in protecting Salmonella from oxidative stress encountered during infection.